2017
DOI: 10.1016/j.freeradbiomed.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Aging-associated metabolic disorder induces Nox2 activation and oxidative damage of endothelial function

Abstract: Oxidative stress attributable to the activation of a Nox2-containing NADPH oxidase is involved in the development of vascular diseases and in aging. However, the mechanism of Nox2 activation in normal aging remains unclear. In this study, we used age-matched wild-type (WT) and Nox2 knockout (KO) mice at 3–4 months (young); 11–12 months (middle-aged) and 21–22 months (aging) to investigate age-related metabolic disorders, Nox2 activation and endothelial dysfunction. Compared to young mice, middle-aged and aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…We demonstrated that ASM down‐regulation indeed inhibited the production of O 2 − , which was mainly derived from ceramide and NADPH oxidase in PA‐induced RAECs. This is consistent with the reports that NADPH oxidase activation damages endothelial function and induces insulin resistance , and PA stimulates the production of ROS through activating NADPH oxidases . Our previous study also demonstrated that ASM mediated the aggregation of membrane raft, forming NADPH oxidase‐mediated O 2 −· production in coronary arterial endothelial cells .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that ASM down‐regulation indeed inhibited the production of O 2 − , which was mainly derived from ceramide and NADPH oxidase in PA‐induced RAECs. This is consistent with the reports that NADPH oxidase activation damages endothelial function and induces insulin resistance , and PA stimulates the production of ROS through activating NADPH oxidases . Our previous study also demonstrated that ASM mediated the aggregation of membrane raft, forming NADPH oxidase‐mediated O 2 −· production in coronary arterial endothelial cells .…”
Section: Discussionsupporting
confidence: 92%
“…We further explored the isoforms of NADPH oxidases to mediate the oxidative stress of ASM in RAECs. Among Nox isoforms, Nox1, 2 and 4 are expressed in vascular endothelial cells , and Nox2 and Nox4 are highly expressed in vascular endothelial cells , which were activated by PA in the current study. It has been shown that ASM and ceramide could activate the Nox2 isoform in non‐muscle cells through enhancing phosphorylation of p47 phox 44 .…”
Section: Discussionsupporting
confidence: 50%
“…In VSMCs, Nox4 downregulation induces senescence [182], while in ECs, reduced Nox4 expression inhibits senescence [183]. Nox2 downregulation was also associated with reduced EC senescence [184]. A more comprehensive review of the role of NADPH oxidases in vascular senescence can be found in our recent review [155].…”
Section: Cigarette Smoke and Nicotine In Senescencementioning
confidence: 93%
“…Mitochondrial targeted antioxidants decrease aortic ICAM in old mice (Zinovkin et al., ), and in rat endothelial cells scavenging of mitochondrial ROS attenuates NFκB activity and inflammatory cytokine production (Ungvari et al., ). The age‐related increase in aortic VCAM is dependent on the NAPDH oxidase subunit Nox2 (Fan et al., ). Leucocyte recruitment to arteries is greater in 9‐month‐old mice that overexpress p22phox in smooth muscle compared with 9‐month‐old control animals (Wu et al., ).…”
Section: Interventions To Ameliorate Age‐related Inflammation and Artmentioning
confidence: 99%
“…Mitochondrial targeted antioxidants decrease aortic ICAM in old mice (Zinovkin et al, 2014), and in rat endothelial cells scavenging of mitochondrial ROS attenuates NF B activity and inflammatory cytokine production (Ungvari et al, 2007). The age-related increase in aortic VCAM is dependent on the NAPDH oxidase subunit Nox2 (Fan et al, 2017).…”
Section: Role Of Ros and Antioxidant Interventionsmentioning
confidence: 99%